2019
DOI: 10.1093/jxb/erz163
|View full text |Cite
|
Sign up to set email alerts
|

Defence gene expression and phloem quality contribute to mesophyll and phloem resistance to aphids in wild barley

Abstract: Aphids, including the bird cherry-oat aphid (Rhopalosiphum padi), are significant agricultural pests. The wild relative of barley, Hordeum spontaneum 5 (Hsp5), has been described to be partially resistant to R. padi, with this resistance proposed to involve higher thionin and lipoxygenase gene expression. However, the specificity of this resistance to aphids and its underlying mechanistic processes are unknown. In this study, we assessed the specificity of Hsp5 resistance to aphids and analysed differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 103 publications
9
77
2
Order By: Relevance
“…Global analysis of aphid feeding patterns indicated that aphid feeding behaviour was significantly affected by plant identity (F 1,43 = 3.19; p = 0.017) and the interaction between endosymbiont presence and plant identity (F 1,43 = 2.71; p = 0.037). From the 72 parameters obtained, seven parameters were affected by plant identity alone (Table S1), however these parameters are not presented or discussed in detail here as we recently characterised R. padi feeding responses to plant identity in a separate study (see Leybourne et al 2019). In support of hypothesis 1, a total of 11 parameters were primarily influenced by endosymbiont infection, and these were mainly associated with stylet intracellular punctures and interaction with the phloem (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Global analysis of aphid feeding patterns indicated that aphid feeding behaviour was significantly affected by plant identity (F 1,43 = 3.19; p = 0.017) and the interaction between endosymbiont presence and plant identity (F 1,43 = 2.71; p = 0.037). From the 72 parameters obtained, seven parameters were affected by plant identity alone (Table S1), however these parameters are not presented or discussed in detail here as we recently characterised R. padi feeding responses to plant identity in a separate study (see Leybourne et al 2019). In support of hypothesis 1, a total of 11 parameters were primarily influenced by endosymbiont infection, and these were mainly associated with stylet intracellular punctures and interaction with the phloem (Table 1; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A faster initiation of sustained feeding could explain the higher mass of H. defensa -infected nymphs on Concerto. However, it is likely that our observed reduction in nymph mass for both infected and uninfected nymphs when feeding on Hsp5 compared with those feeding on Concerto is due increased aphid resistance in Hsp5 (Leybourne et al, 2019). The rapid initiation of sustained feeding could be associated with other aphid fitness effects which are currently uncharacterised, such as the transmission or acquisition of phloem-limited viruses.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We recently compared a modern domesticated cultivar of barley Hordeum vulgare (Linnaeus) cv. Concerto (Concerto) with a wild progenitor species possessing partial-resistance against aphids, H. spontaneum 5 (Linnaeus) (Hsp5) (L EYBOURNE et al 2019). We showed that partial-resistance in Hsp5 primarily involves mesophyll- and phloem-derived resistance factors, associated with increased defence gene expression and a reduction in phloem quality, respectively, which contribute to decreased aphid fitness (L EYBOURNE et al 2019).…”
Section: Introductionmentioning
confidence: 99%